The Odd One Out: Energy is not like Other Metrics - Anand, Vaastav; Xie, Zhiqiang; Stolet, Matheus; Viti, Roberta De; Davidson, Thomas; Karimipour, Reyhaneh; Alzayat, Safya; Mace, Jonathan (HotCarbon 2022: 1st Workshop on Sustainable Computer Systems Design and Implementation, 2022)
Energy requirements for datacenters are growing at a fast pace. Existing techniques for making datacenters efficient focus on hardware. However, the gain in energy efficiency that can be achieved without making the applications energy-aware is limited. To overcome this limitation, recent work has proposed making the software running in datacenters energy aware. To do so, we must be able to track energy consumption at various granularities at the software level – (i) process level; (ii) application level; (iii) end-to-end request level. Currently, existing software energy-tracking techniques primarily focus on tracking energy at the process or application level; only a few techniques track energy at an end-to-end request level. However, not tracking energy at an end-to-end request level can lead to false software optimizations and cause a decrease in energy efficiency. To track energy at an end-to-end request level, we can leverage end-to-end tracking techniques for other metrics such as distributed tracing. However, we posit that energy cannot be treated as just another metric and that we cannot use existing frameworks without modifications. In this paper, we discuss how energy is different from other metrics and describe an energy-tracking workflow that leverages these differences and tracing techniques in order to track energy consumption of end-to-end requests.